Strength of materials and structures - Case, John, 1888-1969 (Arnold ; John Wiley & Sons, 1999)
Starting with basic mechanics, the book goes on to cover numerical techniques such as matrix and finite element methods. There is also additional material on composite materials, thick shells, flat plates, and the vibrations of complex structures. Illustrated throughout with worked examples, the book also provides problems for students to attempt.
Previous edition: 1993.
Includes index.
Keywords: Strength of materials.; Materials -- Analysis.; Structural analysis (Engineering); elektronické knihy; electronic books